2006
DOI: 10.1126/science.1129709
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Light Cues Underlie Compass Calibration in Migratory Songbirds

Abstract: Migratory songbirds use the geomagnetic field, stars, the Sun, and polarized light patterns to determine their migratory direction. To prevent navigational errors, it is necessary to calibrate all of these compass systems to a common reference. We show that migratory Savannah sparrows use polarized light cues from the region of sky near the horizon to recalibrate the magnetic compass at both sunrise and sunset. We suggest that skylight polarization patterns are used to derive an absolute (i.e., geographic) dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
242
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(259 citation statements)
references
References 31 publications
13
242
4
Order By: Relevance
“…Cue-calibration experiments specifically testing this hypothesis by shielding the lower part of the sky from view during the cue-calibration phase confirmed these findings [51,52]. It has to be noted, however, that birds do not always recalibrate their magnetic compass, even when given full access to PL cues near the horizon [55,56].…”
Section: Sunrise and Sunset Polarized Light Cues As Compass Calibratisupporting
confidence: 62%
See 2 more Smart Citations
“…Cue-calibration experiments specifically testing this hypothesis by shielding the lower part of the sky from view during the cue-calibration phase confirmed these findings [51,52]. It has to be noted, however, that birds do not always recalibrate their magnetic compass, even when given full access to PL cues near the horizon [55,56].…”
Section: Sunrise and Sunset Polarized Light Cues As Compass Calibratisupporting
confidence: 62%
“…Evidence for a key role of sunrise and sunset PL cues in compass calibration has also been provided by experiments with migratory songbirds, where PL information was not manipulated during the actual orientation experiment itself, but instead during a calibration period prior to testing [47][48][49][50][51][52][53]. In these studies, birds were exposed to conflicting information between magnetic and PL cues (one of the two cues being artificially deflected relative to the other by either shifting the horizontal component of the geomagnetic field relative to the natural skylight polarization pattern, or alternatively, by artificially shifting the band of maximum polarization relative to the natural magnetic field).…”
Section: Sunrise and Sunset Polarized Light Cues As Compass Calibratimentioning
confidence: 99%
See 1 more Smart Citation
“…True navigation implies that animals orient themselves by relying on cues available at the unfamiliar release site, and these usually are cues with a worldwide geographic distribution such as magnetic cues (Wiltschko and Wiltschko 1995;Lohmann 1991), lightdependent cues (Muheim et al 2006;Phillips et al 2010), infrasound cues (Hagstrum 2000), or odor cues (Jorge 2011;Wallraff 2005). In Experiment 3, we showed that adult L. pholis were able to orient themselves toward their home areas even if they were placed in an unfamiliar distant area, and they did so by relying on cues available in the unfamiliar area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other insects, such as spiders [3] and field crickets [4], have also been shown to use sky polarization for navigation. Migratory birds were found to use the sky polarization at sunrise and sunset in the autumn and spring to calibrate their magnetic compass while passing between different latitudes [5][6][7]. Some even claim that the Vikings, with the aid of a 'sunstone' as a natural polarizer, used the sky's polarization to help them navigate the seas [8].…”
Section: Introduction (A)mentioning
confidence: 99%